2006
DOI: 10.1603/0022-0493-99.5.1525
|View full text |Cite
|
Sign up to set email alerts
|

DNA Screening Reveals Pink Bollworm Resistance to Bt Cotton Remains Rare After a Decade of Exposure

Abstract: Transgenic crops producing toxins from the bacterium Bacillus thuringiensis (Bt) kill insect pests and can reduce reliance on insecticide sprays. Although Bt cotton (Gossypium hirsutum L.) and Bt corn (Zea mays L.) covered 26 million ha worldwide in 2005, their success could be cut short by evolution of pest resistance. Monitoring the early phases of pest resistance to Bt crops is crucial, but it has been extremely difficult because bioassays usually cannot detect heterozygotes harboring one allele for resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 37 publications
0
29
1
1
Order By: Relevance
“…In particular, the laboratory selection experiments with Cry2Ab in diet started with a hybrid strain of pink bollworm (BX-H) that had close to 10% survival at a diagnostic concentration of Cry1Ac (10 g toxin/mL diet) ( Table 1). In contrast, after a decade of exposure to cotton producing only Cry1Ac, survival at the diagnostic concentration of Cry1Ac was essentially 0% in field-derived strains of pink bollworm (24,25). Second, laboratory-selected strains of pink bollworm showed recessive inheritance of resistance to high concentrations of Cry2Ab (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In particular, the laboratory selection experiments with Cry2Ab in diet started with a hybrid strain of pink bollworm (BX-H) that had close to 10% survival at a diagnostic concentration of Cry1Ac (10 g toxin/mL diet) ( Table 1). In contrast, after a decade of exposure to cotton producing only Cry1Ac, survival at the diagnostic concentration of Cry1Ac was essentially 0% in field-derived strains of pink bollworm (24,25). Second, laboratory-selected strains of pink bollworm showed recessive inheritance of resistance to high concentrations of Cry2Ab (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Both Cry1Ac and Cry2Ab are active against some key lepidopteran pests, including pink bollworm (Pectinophora gossypiella), a major cotton pest in the southwestern United States and in many other countries (21). Bt cotton producing only Cry1Ac has been exceptionally effective against pink bollworm in Arizona; susceptibility to Cry1Ac has not decreased in field populations of this pest despite more than a decade of exposure (22)(23)(24)(25). Previous work showed that laboratory selection of pink bollworm with Cry1Ac yielded high levels of resistance to Cry1Ac, but little or no cross-resistance to Cry2A toxins (26-28; http://www.epa.gov/scipoly/sap/meetings/ 2006/october/unnithan et al 04 cry2ab baselines.pdf).…”
mentioning
confidence: 99%
“…Resistance genes of lepidopteran and coleopteran populations exposed to Bacillus thuringiensis spraying or to Bt-transgenic crops have been investigated, and the frequency ranges from 10 Ϫ5 to 10 Ϫ1 (1, 2, 5, 6, 14, 16,19,35,36). Global monitoring data on resistance have shown that the frequency of resistance alleles has not increased in pest insects from Bt crop areas, and it is likely that the high-dose refuge strategy has contributed to delaying resistance (21,34).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies used the F2 screen to estimate the frequency of resistance alleles, which is a method based on the bioassay of F2 neonates obtained from isofemale lineages. Recently the first DNA screening for mutants of the cadherin gene associated with Bt cotton resistance of the pink bollworm Pectinophora gossypiela (Lepidoptera: Gelechiidae) was performed, but those alleles were not present in a sample of 5,571 insects from Arizona (36). A similar screening of a retrotransposon insertion in the cadherin gene (HevCaLP) associated with B. thuringiensis resistance of the lepidopteran Heliothis virescens did not detect this insertion among 7,000 individuals, and its frequency was estimated to be 7 ϫ 10 Ϫ5 (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation